(untitled) (Economic and Political Thought, 2014)
The article is devoted to the process of adoption of a Japanese model by China at the turn of the 19th and the 20th century and its rejection in the years 1915–1937. The article presents the influence exerted on the “Middle State” by Japan in that period and its consequences, including the development of the communist movement in China.